Figurative Language in Sabian Poetry by Oka Rusmini - Eva nurmayani (Tinta Emas Institute, 2025)
This study aims to describe the form of personification in Sabian poetry by Oka Rusmini. Language is a means of communication, expressing oneself, ideas and thoughts by its speakers. Language is also a medium in the creation of works, one of which is literary works in the form of poetry. In addition to having intrinsic and extrinsic elements, poetry also uses figurative language in its creation. This study uses a qualitative description method. Data analysis techniques by examining figurative language data personification, reducing data, classifying data, analyzing data and interpreting data, then concluding. The results of this study indicate that Personification in Sabian Poetry by Oka Rusmini consists of personification of nature and personification of objects. The use of personification in literary works of poetry gives rise to ownership in poets equating nature, inanimate objects or living creatures other than humans with human-like characteristics and characteristics, thereby giving rise to the value of beauty, and imagination and creating emotional closeness between poets and readers, and being able to train readers' sensitivity to the environment.